Evaluation of the efficacy of fractional microneedling radiofrequency combined with PRP for facial atrophic acne scars - Xiaoyan LI; Lei NIE; Wei GUO; Chen LI; Bo SUN; Kefeng LIU; Shaohang CHENG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective: To compare the efficacy of PRP in combination with fractional microneedling radiofrequency or roller microneedle for facial atrophic acne scars. Methods From April 2019 to April 2021, a total of 74 patients with facial atrophic acne scars were randomly assigned to the observation and the control groups. The observation group was treated with fractional microneedling radiofrequency combined with PRP once every 4 weeks for three sessions, while the control group was treated with roller microneedle combined with PRP once every 4 weeks for three sessions. Both groups were followed up for 6 months. ECCA weighting score, clinical efficacy, and adverse effects, were assessed prior to and 6 months after the last treatment. Results Prior to the treatment, there were no significant differences in ECCA weight scores between the two groups (53.38±19.15 in the observation group vs. 52.43±25.94 in the controls, Z=-0.64, P=0.524). Six months after the treatment, the ECCA weight score was markedly decreased in both groups (24.46±14.38 in the observation group, 36.08±20.38 in the controls; Z=-2.20, P<0.05). The overall effective rates in the observation group and controls were 91.89% and 72.97%, respectively (χ2=4.57, P<0.05). The duration of redness and swelling, healing time and absence from work in the observation group were shorter than that in the control group (P<0.05). Conclusion Fractional microneedling radiofrequency combined with PRP is safe and effective for facial atrophic acne scars.